Designing a Bumdes Business Model Based on Canvas and ISM to Support Food Security - Etin Puspita Sari; Mochamad Fatchurrohman; Fajar Tenovita Sari (Jurnal Ilmu Manajemen, 2025)
Village food security is a strategic issue that is not only related to fulfilling the basic needs of the community but is also closely linked to local economic independence. Village Owned Enterprises (BUMDes) play a significant role in strengthening the village economic base through the organized management of local resources. However, weaknesses in business model design often hinder the sustainability and effectiveness of BUMDes. This study aims to design a BUMDes business model based on the Business Model Canvas (BMC) combined with Interpretive Structural Modeling (ISM). The purpose is to comprehensively map business blocks while identifying the hierarchical structure of key success factors of BUMDes in supporting food security. The research employs a combination of qualitative and quantitative descriptive methods. Primary data were collected through questionnaires and interviews with 30 BUMDes in East Java, while the analysis was conducted using BMC mapping and the development of hierarchical relationships among factors through ISM. The findings indicate that the integration of BMC and ISM can formulate a more adaptive and systematic BUMDes business model aligned with local characteristics. The ISM analysis highlights the presence of key driving factors in human resources and strategic partnerships, which are then integrated into the BMC blocks to reinforce the value proposition and revenue streams of BUMDes. This study contributes theoretically by integrating the BM-ISM approach within the context of rural development and offers practical implications in the form of a business model framework that can be utilized by village governments, BUMDes managers, and stakeholders to strengthen food security and foster local economic independence.